Narayan Man Bijukchhen’s Letters from Jail: A Study in Erikson’s Psychosocial Development - Khulimuli, Shiva Bahadur (Bagiswori Journal, 2026)
This research article studies Narayan Man Bijukchhen’s Letters from Jail (2025) written to his wife Shova Pradhan from Nakkhu Jail between 1988 and 1989. These letters depict the scene of various aspects such as culture, family bond, politics, social activities, ethnic/ cultural traditions as well as the final years of the Panchayat System. The depictions from the author are visualized and studied through the lens of Eric Erikson’s psychosocial development theory by adopting a qualitative theory-driven thematic analysis approach. This paper studies Bijukchhen’s selected ten letters out of twenty one to examine how confinement intensifies psychosocial conflicts but also fosters adaptation, reflection, and meaning-making, thereby affirming the human capacity for growth in adversity. The letters disclose how imprisonment disrupts but does not terminate developmental processes, particularly in the stages of identity versus role confusion, intimacy versus isolation, generativity versus stagnation, and integrity versus despair. The writer struggles with isolation yet seeks intimacy, resists stagnation through generative reflection, and pursues integrity by finding meaning in spirituality, culture, and nature. By situating personal suffering within broader societal critiques, the author through the letters portrays resilience in psychosocial development.